Robotics Software Design and Engineering - Rafael Garcia Ramirez, Alejandro; Loureiro da Costa, Augusto (IntechOpen, 2021)
Robotics Software Design and Engineering is an edited volume on robotics. Chapters cover such topics as cognitive robotics systems, artificial intelligence, force feedback, autonomous driving embedded systems, multi-robot systems, a robot software framework for Real-time Control systems, and Industry 4.0. Also discussed are humanoid robots, aerial and work vehicles, and robot manipulators.